2011
DOI: 10.1111/j.1939-1676.2011.0743.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Clinical Trial Assessing the Efficacy of Denamarin for Prevention of CCNU‐Induced Hepatopathy in Tumor‐Bearing Dogs

Abstract: Background: Increases in liver enzymes occur in up to 86% of dogs receiving CCNU and can result in treatment delay or early discontinuation of treatment. Denamarin contains S-adenosylmethionine and silybin, both of which have been investigated as treatments for various liver diseases.Hypothesis: Dogs on CCNU receiving Denamarin have lower alanine aminotransferase (ALT) activity than dogs not receiving Denamarin. Dogs on Denamarin are less likely to require treatment delay because of hepatopathy and are more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 33 publications
5
57
2
4
Order By: Relevance
“…Silybin is an active part of an extract from milk thistle, known as silymarin, and has been shown to support liver function by helping maintain a healthy oxidative balance (17,20). Although silymarin was reported to improve the rate of survival of LPS-treated mice (20), there is no evidence yet to support the use of SAMe, silybin, or both in dogs with endotoxemia.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Silybin is an active part of an extract from milk thistle, known as silymarin, and has been shown to support liver function by helping maintain a healthy oxidative balance (17,20). Although silymarin was reported to improve the rate of survival of LPS-treated mice (20), there is no evidence yet to support the use of SAMe, silybin, or both in dogs with endotoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…and anticoagulant proteins (protein S, protein C, antithrombin). Thus, liver protection in the course of sepsis is crucial to decrease mortality (16,17). Recent studies showed that S-adenosylmethionine (SAMe) and silymarin could prevent liver injury in different clinical conditions (toxininduced hepatopathy and alcohol-induced hepatopathy) (17) by regulating cytokine responses to the primary insult (18).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations